Characterization of yeasts associated with postharvest pineapple peduncle mold - Oreamuno-Fonseca, Patricia (2023)
Introduction. Pineapple peduncle mold is a complex of microorganisms composed of several fungi, bacteria and yeasts, which affect the fruit at the postharvest stage. Objective. To characterize the yeasts associated with postharvest pineapple peduncle mold, and to evaluate the effect of different temperatures on yeast growth during storage. Materials and methods. Morphological characterization of 24 isolates was carried out, subsequently, 9 representative isolates were selected for molecular characterization. To evaluate yeast growth at different temperatures, yeast suspensions in concentrations of 10-6 CFU were placed on Petri dishes with PDA (potatodextrose-agar) medium. The plates were stored in a chamber with temperature at 4°C, 8°C, 12°C, 16°C and 20°C, and the number of colonies was counted at 2, 3, 4 and 5 days after starting the experiment. Results. For the microscopic description, the yeast cells presented round, oval and cylindrical shapes. In the macroscopic description, the shapes of the yeast colonies were round and/or oval. The consistency of non-pigmented yeast colonies was buttery or creamy, while pigmented yeast were mucoid. For molecular description, pigmented yeasts were classified into the following species: Rhodotorula mucilaginosa, R. toruloides, R. diobovata, Sporidiobolus pararoseus and Sporobolomyces carnicolor, and non-pigmented yeasts: Candida intermedia, Meyerozyma guilliermondii and M. caribbica. For the temperature test, it was observed that as the storage temperature decreased by 4°C, in took one more day for yeast colonies to become visible. Conclusion. Similarities were found between the morphology of the isolates, the molecular characterization allowed identifying the presence of species with potential for biocontrol of pathogens associated with molds.